Astrocytic IP3Rs: Beyond IP3R2 - Sherwood, Mark W.; Arizono, Misa; Panatier, Aude; Mikoshiba, Katsuhiko; Oliet, Stéphane H. R. (Frontiers in Cellular Neuroscience, 2021)
Astrocytes are sensitive to ongoing neuronal/network activities and, accordingly, regulate neuronal functions (synaptic transmission, synaptic plasticity, behavior, etc.) by the context-dependent release of several gliotransmitters (e.g., glutamate, glycine, d-serine, ATP). To sense diverse input, astrocytes express a plethora of G-protein coupled receptors, which couple, via Gi/o and Gq, to the intracellular Ca2+ release channel IP3-receptor (IP3R). Indeed, manipulating astrocytic IP3R-Ca2+ signaling is highly consequential at the network and behavioral level: Depleting IP3R2 results in reduced GPCR-Ca2+ signaling and impaired synaptic plasticity; Enhancing IP3R-Ca2+ signaling affects cognitive functions such as learning and memory, sleep, and mood. However, as a result of discrepancies in the literature, the role of GPCR-IP3R-Ca2+ signaling, especially under physiological conditions, remains inconclusive. One primary reason for this could be that IP3R2 has been used to represent all astrocytic IP3Rs, including IP3R1 and IP3R3. Indeed, IP3R1 and IP3R3 are unique Ca2+ channels in their own right; they have unique biophysical properties, often display distinct distribution, and are differentially regulated. As a result, they mediate different physiological roles to IP3R2. Thus, these additional channels promise to enrich the diversity of spatiotemporal Ca2+ dynamics and provide unique opportunities for integrating neuronal input and modulating astrocyte-neuron communication. The current review weighs evidence supporting the existence of multiple astrocytic-IP3R isoforms, summarizes distinct sub-type specific properties that shape spatiotemporal Ca2+ dynamics. We also discuss existing experimental tools and future refinements to better recapitulate the endogenous activities of each IP3R isoform.